Karakteristik Peternak dan Dukungan Penyuluhan dalam Mendukung Kemampuan Manajerial Beternak Sapi Potong di Desa Oepuah Utara - Agustinus Efu; Ture Simamora (Fakultas Pertanian, Universitas Timor, 2021)
The character of the farmer is something that lies in the nature that is contained in a person when someone implements and has courage. The purpose of this study was to analyze how the influence of breeders and livestock extension support on improving the managerial ability of beef cattle in North Oepuah Village, Biboki Monleu District, North Central Timor Regency. The type of research used is the sampling method carried out by purposive sampling. Data collection was carried out using a questionnaire. The results showed the influence of breeders and extension support on the managerial ability of raising beef cattle in North Oepuah Village, namely education, training intensity, appropriateness of extension methods.